2018
DOI: 10.1002/per.2152
|View full text |Cite
|
Sign up to set email alerts
|

Translating Dispositional Resistance to Change to the Culture Level: Developing A Cultural Framework of Change Orientations

Abstract: A fundamental societal challenge is to balance the desire for growth, development, and progress on the one hand and the need for stability and maintenance of the status quo on the other. To better understand how societies deal with this challenge we employ the personality trait of dispositional resistance to change to conceptualize and empirically establish the concept of cultural change orientation. With data from individuals in 27 countries (N = 6487), we identify three culture‐level change orientation dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 107 publications
(218 reference statements)
0
13
0
Order By: Relevance
“…Italy) tend to have a low tolerance for ambiguity and risk-taking. Accordingly, Oreg and Sverdlik (2018) observe that this dimension also reflects a culture's orientation toward change. High uncertainty avoidance cultures have a proclivity for following standard operating procedures, rules, and regulations.…”
Section: Linking Cultural Values To Communication Breakdownsmentioning
confidence: 94%
“…Italy) tend to have a low tolerance for ambiguity and risk-taking. Accordingly, Oreg and Sverdlik (2018) observe that this dimension also reflects a culture's orientation toward change. High uncertainty avoidance cultures have a proclivity for following standard operating procedures, rules, and regulations.…”
Section: Linking Cultural Values To Communication Breakdownsmentioning
confidence: 94%
“…The influence of culture on migration can be studied, taking into account, the indirect effects of culture on societal development. In this regard, studies (Krys et al, 2020;Oreg & Sverdlik, 2018;Skvarciany & Tereštšenkov, 2016) have shown the significant impact that culture has on social progress. For instance, Dan's (2017) study aimed at identifying links between cultural dimensions defined by Hofstede and Schwartz and social progress defined as social progress index.…”
Section: Cultural and Digital Impact On Migrationmentioning
confidence: 99%
“…As Oreg, and Sverdlik, (2018), suggested, resistance to change is often due to fear of altering the traditional way of doing things, repetitive habit, lack of resources, threat to authority and power, fear of unknown results are the reasons behind more resistance towards change in all the societies. Different researches highlight different reasons behind resistance for change (Oreg, and Sverdlik, 2018). Some suggest that social, personal economical factor influence resistance, while other suggests vague relation between personal and organizational goals.…”
Section: Impact Of Culture On Behaviour Of Citizens Of Saudi Arabiamentioning
confidence: 99%